Given equations are,
"\\frac{dx}{(x-y)y^2} = \\frac{dy}{-(x-y)x^2} = \\frac{dz}{z(x^2+y^2)}"
Taking first two,
"\\frac{dx}{(x-y)y^2} = \\frac{dy}{-(x-y)x^2}"
"\\frac{dx}{y^2} = \\frac{dy}{-x^2}"
Integrating both sides , we get
"\\int -x^2dx = \\int y^2dy"
"y^3 = -x^3 + k" (1)
then, "y = (k-x^3 )^{1\/3}"
Taking first and last part,
"\\frac{dx}{(x-y)y^2} = \\frac{dz}{z(x^2+y^2)}"
Putting value of y, we get,
"\\frac{(x^2+y^2)}{y^2x-y^3}dx = \\frac{1}{z}dz"
"\\frac{(x^2+(k-x^3)^{2\/3})}{(k-x^3)^{2\/3}x-(k-x^3)}dx = \\frac{1}{z}dz"
Now integrating both sides, we get
"\\frac{1}{6} (-\\frac{(3 x^2 (\\frac{k - x^3}{k - 2 x^3})^{(2\/3)} 2^{F1(\\frac{2}{3}, \\frac{2}{3}; \\frac{5}{3}; -\\frac{x^3}{(k - 2 x^3)}}} {(k - x^3)^(2\/3)} ) + 2 log(2 x^3 - k) + 2 log(1 - \\frac{x}{(k x^3 - 1)^{(1\/3)}}) - 2 \\sqrt{3} tan^{-1}(\\frac{\\frac{2 x}{(k x^3 - 1)^{1\/3}} + 1}{\\sqrt{3}}) - log(\\frac{x}{(k x^3 - 1)^{1\/3} }+ \\frac{x^2}{(k x^3 - 1)^{2\/3}} + 1)) + C = lnz"
Where "2^{F_1(a,b;c;x )}" is the hypergeometric function
*Integration is done by online calculator as solution by hand is not possible for the differential equation.
Comments
Leave a comment